Formation of probabilistic and statistical worldview among students in the process of teaching the topic "Absolute black body radiation" in groups of academic lyceums with in-depth study of physics (Journal of Pharmaceutical Negative Results, 2022)
The article analyzes the issues of formation of probabilistic-statistical worldview in students studying quantum physics chapter of academic lyceum of physics. In academic lyceums, there is little time devoted to the subject of quantum physics, the content of the topics is not well covered, in the analysis of the topic, the radiation laws of the absolute black body have a probabilistic character, and in the process of studying this topic, the introduction of probabilistic concepts based on Planck's formula and the study of radiation laws, the content of the subject - The ability of the extraction and enrichment to meet the requirements of the principle of consistency has been studied and discussed.